Study on the In Vitro Effects of the Mixtures of Polycyclic Aromatic Hydrocarbons (PAHs) and Heavy Metals on Ethoxyresorufin-O-Deethylase (EROD) Activity in Mossambica tilapia Liver - Han, Da Xiong; Wang, Hai Yan; Yue, Hong Wei; Wang, Su Min; 韩大雄 (SPRINGER, 2013)
National Public Benefit (Ocean) Research Foundation of China [201105013]; Grand Research Foundation of Fujian Province [2011YZ0001-1, 2013J01386]; Scientific Research Foundation of Third Institute of Oceanography, SOA [201221] This paper reports in vitro effects of individual heavy metals (Cd2+, Cu2+ and Hg2+), and PAHs, including benzo[a]pyrene(BaP), indeno[1,2,3-cd]pyrene (IP) and fluoranthene (FL), and their mixtures on ethoxyresorufin-O-deethylase (EROD) activities using a plate-reader method. The results showed that all three metals inhibited EROD activity, while BaP/IP significantly induced the enzyme. However, FL alone decreased EROD activity. Moreover, co-treatment with BaP/IP and heavy metals inhibited PAH-induced EROD activities, while combined exposure to FL and heavy metals induced FL-inhibited EROD activities.